Reducing radiation exposure during atrial fibrillation ablation using lectures to promote awareness - Yosuke Miwa; Akiko Ueda; Michitsugu Komeda; Shinsuke Takeuchi; Mika Nagaoka; Yuichi Momose; Noriko Nonoguchi; Kyoko Hoshida; Mutsumi Enomoto; Ikuko Togashi; Akiko Maeda; Yo Hagiwara; et al. (Open Heart)
Objective Recently, concern has increased regarding the hazards of radiation exposure in patients and laboratory staff. Since the numbers of complex catheter ablations (CA) performed, duration of procedure times, and need for multiple sessions have increased, radiation exposure during each session needs to be minimised. Our study aimed to assess the impact of awareness on radiation exposure during CA for atrial fibrillation (AF).Methods Mini-course lectures was delivered to the physicians and staff in the electrophysiology division. Its effect on the fluoroscopic time and radiation dose during AF ablation before (Group I, n=70), shortly after (Group II: n=70) and remotely after the mini-lecture (Group III, n=70) were evaluated. Patient demographics, preoperative testing and procedural parameters were collected.Results The fluoroscopic time significantly reduced after the lecture (Group I and II: 25.1±10.0 and 15.1±7.3 min, respectively (p<0.0001)), and remained so in Group III (13.0±5.4 min), despite the increase in the number of persistent AFs. The radiation dose also significantly reduced (Groups I, II, III: 295.0±263.0, 109.6±103.5 and 110.1±89.6 mGy, respectively (p<0.0001)).Conclusion Awareness on radiation exposure led to a significant reduction in fluoroscopic time and radiation dose during CA for AF, the effect of which persisted even to remote periods following the procedure.